1993
DOI: 10.1073/pnas.90.2.522
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines, endotoxin, and glucocorticoids regulate the expression of inducible nitric oxide synthase in hepatocytes.

Abstract: Nitric oxide (NO-) is a short-lived mediator which can be induced in a variety of cell types and produces many physiologic and metabolic changes in target cells. The inducible or high-output NO' synthase (NOS) pathway was first characterized in macrophages activated by lipopolysaccharide (LPS) and interferon v (IFN-y). Hepatocytes also express an inducible NOS following exposure to the combination of endotoxin (LPS) and tumor necrosis factor (TNF), interleukin 1 Following the discovery of the nitric oxide (NO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
301
4
8

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 599 publications
(336 citation statements)
references
References 36 publications
23
301
4
8
Order By: Relevance
“…We previously showed that DEX inhibits inducible nitric oxide synthase gene expression and nitric oxide production in cultured primary hepatocytes stimulated with TNF-a and interleukin-1b by suppressing NF-kB activation. 34,35 Furthermore, DEX can inhibit the production of proinflammatory cytokines in immune cells by the suppression of NF-kB activation. 5 We found that pretreatment of hepatocytes with DEX for 2-12 h inhibited NF-kB activation, as determined by gel-shift assay, in cultured rat primary hepatocytes stimulated with TNF-a (data not shown), suggesting that DEX-mediated upregulation of cFLIP is not due to NF-kB activation.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that DEX inhibits inducible nitric oxide synthase gene expression and nitric oxide production in cultured primary hepatocytes stimulated with TNF-a and interleukin-1b by suppressing NF-kB activation. 34,35 Furthermore, DEX can inhibit the production of proinflammatory cytokines in immune cells by the suppression of NF-kB activation. 5 We found that pretreatment of hepatocytes with DEX for 2-12 h inhibited NF-kB activation, as determined by gel-shift assay, in cultured rat primary hepatocytes stimulated with TNF-a (data not shown), suggesting that DEX-mediated upregulation of cFLIP is not due to NF-kB activation.…”
Section: Discussionmentioning
confidence: 99%
“…NO production by inducible NOS (iNOS) in the liver, in contradistinction to eNOS generation of NO, is independent of calcium and largely dependent on the level of iNOS gene expression. 41 Although the liver is not thought to express iNOS basally, every major cell type in the liver expresses iNOS under appropriate circumstances, particularly the hepatocyte. 42 TNF-␣, interleukin 1␤, and interferon gamma all have the capability to induce iNOS transcription in hepatocytes, although IL-1 is the most potent in human and rat hepatocytes.…”
Section: Control Of Vascular Tone In the Mesenteric Portal And Systmentioning
confidence: 99%
“…In vitro, interleukin-1 (IL-1), tumor necrosis factor (TNF), interferon-γ (IFN-γ), and bacterial lipopolysaccharide (LPS) act synergistically to induce iNOS expression maximally in hepatocytes. [15] Interleukin-1 is the most potent single inducer of iNOS, [16] while redox stress further activates iNOS gene transcription. [11] In vivo, hepatocyte iNOS expression has been identified in response to endotoxemia, [17] hemorrhagic shock, [18,19] hepatic and intestinal ischemia/reperfusion, [20] and during hepatic regeneration [21] or hepatitis.…”
Section: Nitric Oxide Synthesis and The Livermentioning
confidence: 99%